"Eat, my child." Obesity among children in developing countries: Evidence from South Africa. Issue 4 (14th July 2020) - Minos, Dimitrios
Abstract: Childhood obesity in developing countries is a topic that has not yet been adequately covered in the literature. Although obesity is rising worldwide and is very present even among the poorest of households in developing countries, most of the attention is still given to industrialized ones. This exploratory paper utilizes the South African National Income Dynamics Study panel data set to highlight some of the aspects policymakers should bear in mind. In particular, policy options targeting mothers may not be appropriate in a developing setting. Higher attention should be given to caregivers instead. The results of the fixed effects probability regressions indicate that having a nonobese, well‐educated caregiver could potentially reduce the probability of a child being obese, thus informing policymakers about potential target groups and channels.